Flexing In Social Media: Between Confession and Conflict in an Islamic Perspective - Muhammad Arga Pramudya; Tangguh Okta Wibowo; Magaretha Indriani; Mohammad Azis Fadhlul Rahman; Khairul Syafuddin (Sahafa Journal of Islamic Communication, 2023)
Flexing behavior or flaunting wealth on social media has become a common phenomenon that can have a negative impact. Driven by the ease of sharing on social media, people tend to compete to flaunt their possessions in order to gain recognition and praise from others. Therefore, this study wants to find out more about how this flexing phenomenon is understood through the subjects studied. This study used a qualitative approach with a descriptive research type. The result of this study is that flexing behavior has a negative impact on the mental health of the individuals involved, due to the lack of validation and acceptance in the social environment. Even though there are views that take advantage of flexing in marketing, in Islamic economics this culture is still considered excessive and contrary to Islamic rules. Therefore, social media users need to understand the prohibition and build an identity without a flexing strategy.